PCR screening of tick-borne agents in sensitive conservation areas, Southeast Portugal - Santos-Silva, M.M. (2021)
The Southeast region of Portugal, particularly the Guadiana valley, is currently the reintroduction territory of Lynx pardinus (Iberian lynx), one of the most endangered felids in the world that is only found in the Iberian Peninsula. Over the last century, populations have declined, placing L. pardinus at extremely high risk of extinction in the wild and relying on reintroduction projects. Among the aspects taken into account in the establishment of new populations is the sanitary status of the selected habitats, especially concerning infectious diseases, including tick-borne pathogens (TBPs). This study presents the results of TBPs survey on ticks collected at sensitive conservation areas of Southeast Portugal. From 2012 to 2014, 231 ticks obtained from vegetation, sympatric domestic and wild animals were submitted for analysis. The presence of Babesia spp., Cytauxzoon spp., Theileria spp., Hepatozoon spp., Anaplasma spp., Ehrlichia spp., Candidatus Neoehrlichia mikurensis, among other Anaplasmataceae, and Coxiella burnetii were investigated by PCR. Six tick species were recorded, Dermacentor marginatus (n = 13/5.6%), Hyalomma lusitanicum (n = 175/75.8%), Ixodes ricinus (n = 4/1.7%), Rhipicephalus bursa (n = 7/3.0%), R. pusillus (n = 21/9.1%) and R. sanguineus sensu lato (n = 11/4.8%). The molecular screening confirmed the presence of two tick-borne pathogens, C. burnetii (N = 34) and Anaplasma platys (N = 1), and one tick-endosymbiont, Candidatus Midichloria mitochondrii (N = 45). The results obtained provide new information on the circulation of ticks and TBPs with potential veterinary importance in Iberian lynx habitat.